Effectiveness of bio-insecticide incorporated storage bag for safe storage of legumes - DUBEY, ABHINAV; MANI, INDRA; NEBAPURE, S M; SHARMA, P K; PARRAY, ROAF AHMAD; RUDRA, SHALINI GAUR; V, ARUN KUMAR T; ALAM, WASI; SINGH, MUKESH KUMAR (The Indian Journal of Agricultural Sciences, 2022)
India loses 2–6% of total produce due to lack of improper farm storage facilities. A potential novel method ofincorporating the bioinsecticide (azadirachtin 0.15%) into the storage bag was evaluated for its effectiveness in insect control for safe pulse storage at Division of Agricultural Engineering, ICAR-Indian Agricultural Research Institute, New Delhi during 2021. Azadirachtin (2.41%) was incorporated into jute and woven polypropylene bag. The configuration with both sides treated jute and WPP bag produced mortality of 93 and 100% respectively against Callosobruchus maculatus adults. Both the treated bags produced mortality (>75%) within 48 h indicating the efficacy of selected bioinsecticide to contain infestation. The contact toxicity was dependent on porosity and pH of the storage bag material along with exposure time. Incorporation of the bioinsecticide saved more than 30% loss of weight in Bengal gram stored for 6 months. The storage quality of legumes, accessed as percentage of grains with holes and percentage of grains with eggs after storage duration of six months was within the acceptable values. The practice saved a value of `3242/t on stored Bengal gram in Jute bag and `206 in WPP bag respectively. Thus incorporation of azadirachtin could be potential tool for effective post-harvest storage of legumes in a sustainable manner.